Socioeconomic determinants of breastfeeding practices in South India - A hospital-based cross-sectional study - Naaraayan, Sridevi A; Priyadharishini, Dorairaj; Geetha, R; Vengatesan, A (Indian Journal of Child Health, 2018)
Background: Breastfeeding is an unparalleled universally recommended intervention for the promotion of health and nutrition of children and reduction of mortality. In spite of the WHO recommendations and baby-friendly hospital initiative, breastfeeding practices are inappropriate due to maternal, infant, socioeconomic, and cultural factors. Objective: The objective of this study was to determine the socioeconomic factors associated with inappropriate breastfeeding practices. Secondary objective was to determine the knowledge level of mothers on ideal breastfeeding recommendations. Materials and Methods: This cross-sectional study was conducted in pediatric wards of a tertiary care teaching institution from January 2017 to July 2017. Mothers having children aged 7–60 months were included in the study. A sample size of one thousand was planned. After obtaining informed consent from mother, detailed feeding history including the timing of initiation of breastfeeding following childbirth, duration of exclusive breastfeeding, and age at which breastfeeding was discontinued was noted. Possible determinants considered were gender of the child, place of residence, maternal age, maternal education, maternal employment, number of children at home, type of family, whether mother was counseled during antenatal period, mode of delivery, and hospitalization in newborn period. Knowledge of mother on breastfeeding was probed and the response recorded. Univariate analysis followed by regression was performed to determine the significant factors. Results: 59% (95% confidence interval 55.9–62.1) of mothers initiated breastfeeding within 1 h of childbirth. 70.2% (95% CI - 67.3–73) exclusively breastfed their babies for 6 months and above. 43.6% (95% CI - 39.2–48.1) of mothers with children of age 25–60 months breastfed their babies up to 2 years and beyond. On univariate analysis, female gender, maternal employment, operative delivery, and hospitalization in the newborn period were identified as risk factors for inappropriate breastfeeding practices, which were confirmed by regression. Overall, only 26.6% (95% CI - 23.9–29.5) of mothers had appropriate knowledge about ideal breastfeeding recommendations. Conclusion: Female gender, maternal employment, operative delivery, and hospitalization in newborn period are significant independent risk factors for inappropriate breastfeeding practices. Only a quarter of mothers had adequate knowledge of breastfeeding recommendations.